A Holistic Examination Of Challenges, Strategies, And Solutions For Empowering Women Entrepreneurs: A Bibliometric Analysis: EMPOWERING WOMEN ENTREPRENEURS: A BIBLIOMETRIC ANALYSIS - Rida; Dr. Muhammad Shahbaz; Dr. Muhammad Adnan Sial; Muhammad Rasheed, (Dialogue Social Science Review (DSSR), 2025)
The complexities and adversities confronting female entrepreneurs is being sought to be identified through a wide range of research papers which has been outlined in this footnote bibliography. It examines the gender landscape within the diverse stages of entrepreneurship by pointing out the factors that stop women like limited access of funding, poor networking, juggling family duties in perception of society. Besides this, the literature review section expands on the impacts of these elements and split the experiences of female entrepreneurs across the world to show the varied ways in which this is manifested. It captures resource rich ideas, state of the art and employing strategic approaches when dealing with the barriers and inclusion ecosystem. The study depicted from 749 Scopus database papers published between 2014 to May 2nd, 2024. The sample procedure was performed using the PRISMA method. First of all, the articles were shortlisted limit to the keyword’s women entrepreneurs or women entrepreneurship and challenges or barriers. The limit is only for the subject area social sciences. The remaining dataset was sorted with an emphasis on articles based on document type and language. The software program VOS viewer, which is used to visualize bibliometric networks, enabled a co-occurrence keyword analysis to identify the most significant themes. In order to provide a systematic approach to data analysis and interpretation, this procedure was followed by creating a table by pivoting and sorting the Scopus database. The results also show that 33 publications done in international journal of gender and entrepreneurship. The six clusters that were taken from the Scopus database systematically captured attention to the repeated terms entrepreneur and entrepreneurship. The highest number of publications done in 2023. In terms of the total number of published publications, the US and UK were tied for first place, but the UK had more citations